Insights into the interaction of ulipristal acetate and human serum albumin using multi-spectroscopic methods, molecular docking, and dynamic simulation. Issue 11 (24th July 2019) - Gan, Na; Sun, Qiaomei; Zhang, Man; Tang, Peixiao; Zhao, Ludan; Xie, Tonghui; Zhang, Yongkui; Li, Hui
Abstract: Interaction between ulipristal acetate (UPA) and human serum albumin (HSA) was investigated in simulated physiological environment using multi-spectroscopic and computational methods. Fluorescence experiments showed that the quenching mechanism was static quenching, which was confirmed by the time-resolved fluorescence. Binding constants ( K a ) were found to be 1 × 10 5 L mol −1, and fluorescence data showed one binding site. Thermodynamic constants suggested the binding process was mainly controlled by electrostatic interactions. Results from the competition experiments indicated that UPA bound to site I of HSA. Fourier transform infrared spectra, circular dichroism spectra, synchronous fluorescence spectra, and 3D fluorescence indicated that UPA can induce conformation change in the HSA. The content of α-helix and β-sheet increased, while β-turn decreased. Hydrophobicity around the tryptophan residues declined, whereas its polarity increased. Molecular docking results were consistent with the experimental results. Results suggested that UPA located at the hydrophobic cavity site I of HSA, and hydrophobic force played the key role in the binding process. Moreover, molecular dynamics simulation was performed to determine the stability of free HSA and HSA-UPA system. Results indicated that UPA can stabilize HSA to a certain degree and enhance the flexibility of residues around site I. Communicated by Ramaswamy H. Sarma GRAPHICAL ABSTRACT: Communicated by Ramaswamy H. Sarma